La cláusula penal en el contrato de promesa de compraventa y su incidencia en la indemnización de daños y perjuicios, en las sentencias dictadas por la corte nacional de justicia, en la sala especializada de lo civil y mercantil de la ciudad de Quito, año 2015. - Chango Vilema, Grace Adriana (2017)
"THE CRIMINAL CLAUSE IN THE CONTRACT OF PROMISE OF SALE AND ITS INCIDENCE IN THE COMPENSATION OF DAMAGES AND INJURIES, IN THE SENTENCES DICTED BY THE NATIONAL COURT OF JUSTICE, IN THE SPECIALIZED ROOM OF THE CIVIL AND COMMERCIAL OF THE CITY OF QUITO, YEAR 2015 . " ABSTRACT: Although the contract of sale is not the central theme of the investigation, there is a need to treat it, since the promise that is one of the variables refers to this contract, so you must know it to understand the subject thoroughly. In this way, a study on the sale contract is carried out, to later refer to the promise of sale as the central theme of the research work. The contract of sale is without a doubt the contract of greater use, because it is perfected daily in any transaction. The contract of sale is basically one by which one of the parties called seller, TRANSFER the tradition of his property to another person called buyer, who must pay a price for this well, from which it will be considered owner of the property, to use it and abuse it. Once the purchase and sale has been explained, the purchase and sale promise will be reviewed as the central theme of the work and variable of the same, for which it will deepen its content, requirements and the legal effects that can cause as would be the case of the constitution in default in case of non-compliance and the penal clause. As a second variable of the investigation will be referred to the action of damages, as an action before the breach of the promise of sale. The action for damages is an action that allows the compensation of damages caused by the breach of the obligation of one of the contractual parties, in the event that this non-compliance has led to economic damage.